A novel single‐base deletion of the RUNX Family Transcription Factor 2 gene associated with cleidocranial dysplasia. (4th January 2023) - Pan, Yuhua; Lu, Wanyu; Meng, Weidong; Liao, Wenxiao; Hu, Aiqin; Wu, Buling; Xiong, Fu
Abstract: Cleidocranial dysplasia (CCD) is a rare, autosomal dominant hereditary disorder characterized by skeletal malformations and dental abnormalities. The purpose of this study was to explore the functional role of a novel mutation in the pathogenesis of CCD. Genomic DNA was extracted from peripheral blood mononuclear cells collected from family members of a Chinese patient with CCD. An analysis of their RUNX Family Transcription Factor 2 ( RUNX2 ) gene sequences was performed by PCR amplification and Sanger sequencing. The function of the mutant RUNX2 was studied by bioinformatics, real‐time PCR, western blotting, and subcellular localization analysis. Sanger sequencing identified a novel single‐base deletion (NM_001024630.4:c.132delG;NP_001019801.3: Val45Trpfs * 99) in the RUNX2 gene present in the Chinese patient with CCD. In vitro, functional studies showed altered protein localization and increased expression of mutant RUNX2 mRNA and mutant Runt‐related transcription factor 2 (RUNX2). Luciferase reporter assay demonstrated that the novel RUNX2 mutations significantly increased the transactivation activity of RUNX2 on the osteocalcin gene promoter. In conclusion, we identified a patient with sporadic CCD carrying a novel deletion/frameshift mutation of the RUNX2 gene and performed screening and functional analyses to determine the cause of the CCD phenotype. This study provides new insights into the pathogenesis of CCD.3